Anna Maenchen papers - Maenchen, Anna.
Chiefly letters from Anna Freud to Maenchen concerning child analysis. Also includes letters from August Aichhorn, Dorothy T. Burlingham, Margit Freud, and Jeanne Lampl-de Groot; an organizational plan and circular letter from the Wiener Psychoanalytische Vereinigung; and a partial draft of a speech written by Maenchen in 1974 titled, "Some thoughts on the psychoanalyst today."
Psychoanalyst. Born 1902; died 1991.
Collection material in English and German.
Forms part of: Sigmund Freud collection.
Keywords: Aichhorn, August, -- 1878-1949 -- Correspondence; Burlingham, Dorothy T. -- Correspondence; Freud, Anna, -- 1895-1982 -- Correspondence; Freud, Margit -- Correspondence; Lampl-de Groot, Jeanne -- Correspondence; Wiener Psychoanalytische Vereinigung; Child analysis; Psychoanalysis; Psychoanalysts